2016
DOI: 10.1111/geb.12490
|View full text |Cite
|
Sign up to set email alerts
|

Realized climate niche breadth varies with population trend and distribution in North American birds

Abstract: Aim Ecological niche theory states that realized niche breadth should increase with population growth. This relationship has been studied extensively in the context of density‐dependent habitat selection, and there is evidence that animal populations at higher density occupy a wider range of vegetation types. To our knowledge, no previous studies have investigated the relationship between population growth and climate niche breadth (i.e. the range of climatic conditions occupied). Here we aim to estimate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…ese birds travel for a long distance from wintering to breeding grounds and any failure in nesting habitats would disturb whole life cycles. Consequently, the selection of nest location is considered the main adaptive response to a combination of climatic conditions [8,9], nest predation pressure [10][11][12], and human disturbances [13,14]. Its selection is therefore vital for individual fitness.…”
Section: Introductionmentioning
confidence: 99%
“…ese birds travel for a long distance from wintering to breeding grounds and any failure in nesting habitats would disturb whole life cycles. Consequently, the selection of nest location is considered the main adaptive response to a combination of climatic conditions [8,9], nest predation pressure [10][11][12], and human disturbances [13,14]. Its selection is therefore vital for individual fitness.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies are showing that niche breadth can impact multiple population and species parameters (Gómez-Rodríguez et al 2015, Saupe et al 2015, Qiao et al 2016, Ralston et al 2016, Rolland and Salamin 2016. However, it is also evident that a complex structure of environmental data, such as autocorrelation, makes it challenging testing the hypotheses on relationships between niche breadth and species distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biotic factors can strongly influence local species distributions (Jablonski, ), and some studies have shown macroecological signals of such species interactions (Gotelli, Graves, & Rahbek, ). Further research may integrate biotic factors including species interactions such as competition (Mordecai, Jaramillo, Ashford, Hechinger, & Lafferty, ), specialization (Fjeldså & Lovett, ), population and community dynamics (Locey & Lennon, ; Ralston, DeLuca, Feldman, & King, ), distributional shifts (Knowles & Massatti, ) and niche differentiation (Brown et al, ). A key question is whether and how such factors contribute to the origins and maintenance of species endemism in some areas and not in others that share similar environmental characteristics.…”
Section: Discussionmentioning
confidence: 99%